The relationship between psychological androgyny and attitudes towards women, self-actualization, and concepts of adjustment - Finlay, Helen Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 1983)
In accordance with American findings, it was proposed that androgynous individuals would be more liberal in their attitudes towards women and more self-actualizing than sex-typed individuals, and that they would tend to conceptualize the well-adjusted person as androgynous, while the sex-typed individual would tend to conceptualize such a person as masculine. It was further hypothesized that sex differences in favour of the female subjects would be found on the first two variables. The Bern Sex-Role Inventory, Shostrom's Personal Orientation Inventory and Spence and Helmreich's Attitudes Toward Women Scale were applied to 192 school counsellors in training and in the field. The hypotheses regarding an androgynous as opposed to a sex-typed orientation on the variables attitudes toward women and self-actualization were not supported; nor were sex-typed individuals found to conceptualize a well-adjusted person as masculine . Sex differences in favour of female subjects were found on the Attitudes Toward Women Scale and on some of the Personal Orientation Inventory scales, and androgynous subjects were found to hold an androgynous model of adjustment.
Keywords: Androgyny (Psychology); Sex differences (Psychology); Self-actualization (Psychology)